2020
DOI: 10.1212/wnl.0000000000010282
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypokinetic-rigid syndrome following SARS-CoV-2 infection

Abstract: OBJECTIVE:To report a case of a patient infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) who acutely developed a hypokinetic-rigid syndrome.METHODS:Patient data were obtained from medical records from the “Hospital Universitario 12 de Octubre” in Madrid, Spain. [123I]-ioflupane dopamine transporter single-photon emission CT (DaT-SPECT) images were acquired 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 18 publications
5
155
1
2
Order By: Relevance
“… Scullen T et al [ 178 ],reported a case of non-convulsive status epilepticus. Movement disorders 18 Generalized Myoclonus, Hypokinetic-rigid syndrome 2 Articles [ 182 ], [ 183 ] 4 3M 1F 71.25(58–88) CNS Vasculitis 19 CNS Vasculitis 2 Articles [ 98 ] [ 185 ], 2 NR in all articles. Cranial Nerve abnormalities 20 Anosmia 28 Articles [ 39 ], [ 56 ], [ 57 ], [ 58 ], [ 62 ], [ 69 ], [ 101 ], [ 182 ], [ 183 ], [ 198 ], [ 199 ], [ 200 ], [ 201 ], [ 202 ], [ 203 ], [ 204 ], [ 205 ], [ 206 ], [ 61 ], [ 207 ], [ 208 ], [ 209 ], [ 210 ], [ 211 ], [ 212 ], [ 213 ] [ 214 ], 3730 NR in all articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Scullen T et al [ 178 ],reported a case of non-convulsive status epilepticus. Movement disorders 18 Generalized Myoclonus, Hypokinetic-rigid syndrome 2 Articles [ 182 ], [ 183 ] 4 3M 1F 71.25(58–88) CNS Vasculitis 19 CNS Vasculitis 2 Articles [ 98 ] [ 185 ], 2 NR in all articles. Cranial Nerve abnormalities 20 Anosmia 28 Articles [ 39 ], [ 56 ], [ 57 ], [ 58 ], [ 62 ], [ 69 ], [ 101 ], [ 182 ], [ 183 ], [ 198 ], [ 199 ], [ 200 ], [ 201 ], [ 202 ], [ 203 ], [ 204 ], [ 205 ], [ 206 ], [ 61 ], [ 207 ], [ 208 ], [ 209 ], [ 210 ], [ 211 ], [ 212 ], [ 213 ] [ 214 ], 3730 NR in all articles.…”
Section: Resultsmentioning
confidence: 99%
“…Seizure 20 Articles [39], [58], [60], [63], [101], [150], [166], [167], [168], [169], [170], [171], [172], [173], [174] (continued on next page) [56], [57], [58], [62], [69], [101], [182], [183], [198], [199], [200], [201], [202], [203], [204], [205], [206], [61], [207], [208], [209], [210], [211], [212] [56], [57], [58], [61], [62], [69], [200], [201] [203] [204], [205], [206],…”
Section: Seizure 17mentioning
confidence: 99%
See 1 more Smart Citation
“…7. A single case report of a patient who developed myoclonus and an acute but spontaneously reversible hypokinetic rigid syndrome, with DaTscan showing reduction of dopamine transporter uptake in the putamen as well as hyposmia 119 . 8.…”
Section: Hyposmia Is Well Documented In Covid-19 Patients Withoutmentioning
confidence: 99%
“…Although encephalitis has been described as a cardinal neurological manifestation of COVID-19 during the acute phase of illness [8,9], we have yet to encounter any of these associated movement disorder presentations. (In the time since this write-up was first prepared, patients with acute movement disorders and COVID-19 have been reported exiguously; we know of four such reports, which describe myoclonus [10,11], a hypokinetic-rigid syndrome [12], and tremor/ataxia [13]. Encephalitis was present in some of those patients.…”
Section: New Observations Lettermentioning
confidence: 99%